Modal Sosial dan Pendampingan BUMDes Sebagai Solusi Recovery Economy Masyarakat Terdampak Tsunami Selat Sunda di Kabupaten Pandeglang - Suhroji Adha; Irawan Irawan; Djaka Adiwinata; Enji Azizi; Mira Nurhikmat; Yulaikah Yulaikah (Jurnal Pengabdian Pada Masyarakat, 2022)
SOCIAL CAPITAL AND ASSISTANCE FOR BUMDES AS ECONOMIC RECOVERY SOLUTIONS FOR COMMUNITIES AFFECTED BY THE SUNDA STRAIT TSUNAMI IN PANDEGLANG REGENCY. The presence of the Ministry of Villages, Development of Disadvantaged Regions and Transmigration is the implementing agent of Law no. 6 of 2014 concerning Villages, it is substantively expected to be able to build villages through structural and cultural approaches. Villages are expected to become independent economically, socially, culturally and politically. The method used in this community service activity is using the lecture method, discussion method, dialogue, and mentoring and practice methods, the material presented about good BUMDes management information is still lacking, this is indicated by a score of 47%., After the community is given education and assistance in the management of BUMDes as the goal of economic recovery after good results were obtained, which was 93%. These results need to be strengthened by improving the management of BUMDes, where academics and the government can collaborate on the best model (deliberative model) for the development of BUMDes to be efficient and competitive.